Different Approaches to Merchandise Trade Balance in Pakistan: An Econometric Evidence (Global Business Management Review (GBMR), 2020)
The current study empirically examines the three major approaches to trade balance for Pakistan by utilizing the yearly data from 1972 to 2016. Monetary, elasticity, and absorption approaches were tested by developing a model that incorporates all three approaches. The significant contribution of the study is that it uses only the merchandise trade deficit account, which includes trade of only physical goods. The study used time-series data; therefore, variables have been tested for the stationarity, and it is found that there is a combination of I (0) and I (1) variables, so ARDL bounds testing approach to co-integration has been employed to find the short run and long run associations among the variables. The bound test results discovered that there is a presence of stable long-term association among the merchandise trade deficit account, real broad money supply, real effective exchange rate, and real domestic absorption. The results further revealed that merchandise trade discrepancy is determined purely by the real effective exchange rate, which specifies that the exchange rate's devaluation increases the deficit in the long run whereas in the short-run increase in domestic absorption decreases the merchandise trade deficit.